Acute asthmatic attack at the pediatric emergency room - Tuazon, Alexander O.; Balbin, Yolanda R.
A retrospective review of children (6 months to 14 years of age) with Acute Asthmatic Attack (AAA) presenting at the Pediatric Emergency Room (PER) covering a 10 month period yielded 123 charts It was found that practice patterns with respect to documentation of severity of illness, medications, and documentation of efficacy of therapy fell short of the current recommendations regarding management of Asthma Asthma continues to pose an important problem in general practice. The erratic fashion in which asthma severity appears to have been assessed are causes for concern. Physicians as well as patient education have a key role in achieving the goals of asthma therapy.
Acta Medica Philippina,1994 30 ( 1 ) pages 29-34
Keywords: Asthma; Child